The resistance to the extension of passes to African women: 1954-1960 - De Villiers, Richard (My University, 1979)
At the annual conference of the African National Congress (ANC) in January 1959, a National Anti-Pass Planning Council was appointed, and the year 1959 declared "Anti-Pass Year". From the inception of the ANC, to its banning in 1960, passes for Africans is a continuous theme of ANC protest activity. Albert Luthuli writes of the early years of the ANC: things were beginning to move. In the Free State in 1913 there were widespread anti-pass demonstrations and numerous arrests. In 1919 Congress organised an anti-pass campaign - in Johannesburg alone there were 700 arrests. But in 1959 passes have become the major focus of ANC opposition to Apartheid. It was this decision; to centre protest against Apartheid specifically around the issue of passes, which finally culminated in the shootings at Sharpeville in March 1960 and launched the crises of the early 1960's for the South African State. This paper seeks to explain why the ANC adopted the Natives Abolition of Pases Act of 1952 as its major thrust of protest activity in 1959. It examines the Anti-Pass Campaign led by the Federation of South African Women (F.S.A.W.) prior to the adoption by the ANC of an anti-pass campaign. Most previous efforts to explain the events leading up to the Sharpeville crisis have not looked at the campaign of the F.S.A.W., nor the general resistance to passes by African women, which began in 1955. The F.S.A.W.'s campaign is generally ignored as a factor influencing the ANC decision, and yet it is probably more significant than any other.
African Studies Seminar series. Paper presented September, 1979
Keywords: Women. Legal status, laws, etc. South Africa; Government, Resistance to. South Africa; South Africa. Politics and government